Influence of Pulse Laser Energy on Structural and Magnetic Properties of CoFe2O4 and CoLa0.01Fe1.99O4 Thin Films. (14th March 2023) - Ismail, Mukhlis M.; Shaker, Suaad S.; Kamil, Raghad A.
Abstract : Cobalt ferrite and CoLa0.01 Fe1.99 O4 thin film were prepared using the pulsed laser deposition method with varying pulse laser energy. XRD analysis was used to investigate the structure of ferrite thin films. The study was expanded to include morphology and magnetic properties. The prepared films showed a strong peak at (311), which belongs to the cubic spinel cobalt ferrite phase with the presence of some peaks belonging to α-Fe2 O3 as hematite phase that depressed when doping with La ion, and the crystallization improvement significantly after intensity increases by increasing the pulsed laser energy from 500 to 650 mJ. The lattice constant of Cobalt ferrite thin films increased with the increase in the laser pulse energy while the crystallite size deduced from the Williamson Hall method showed decreases with the increases of pulse laser energy. The saturation, remnant magnetization, and coercivity of prepared films were studied according to increasing pule laser energy and Lanthanum doping.